Implementation and Early Utilization of a Suicide Hotline for Veterans - Knox, Kerry L. (American Public Health Association, 2012)
Suicide crisis lines have a respected history as a strategy for reducing deaths from suicide and suicidal behaviors. Until recently, however, evidence of the effectiveness of these crisis lines has been sparse. Studies published during the past decade suggest that crisis lines offer an alternative to populations who may not be willing to engage in treatment through traditional mental health settings. Given this promising evidence, in 2007, the Department of Veterans Affairs in collaboration with the Department of Health and Human Services’ Substance Abuse and Mental Health Administration implemented a National Suicide Hotline that is staffed 24 hours a day, 7 days a week, by Veterans Affairs clinical staff. We report here on the implementation of this suicide hotline and our early observations of its utilization in a largely male population.